Regulation of breast tumorigenesis through acid sensors - Gupta, Subash C. (Oncogene, 2015)
The low extracellular pH in the microenvironment has been shown to promote tumor growth and metastasis, however, the underlying mechanism is poorly understood. Particularly, little is known how the tumor cell senses the acidic signal to activate the acidosis-mediated signaling. In this study, we show that breast cancer cells express acid-sensing ion channel 1 (ASIC1), a proton-gated cation channel primarily expressed in the nervous system. RNA interference, knockout and rescue experiments demonstrate a critical role for ASIC1 in acidosis-induced reactive oxidative species and NF-κB activation, two key events for tumorigenesis. Mechanistically, ASIC1 is required for acidosis-mediated signaling through calcium influx. We show that as a cytoplasmic membrane protein, ASIC1 is also associated with mitochondria, suggesting that ASIC1 may regulate mitochondrial calcium influx. Importantly, interrogation of the Cancer Genome Atlas breast invasive carcinoma dataset indicates that alterations of ASIC1 alone or combined with other 4 ASIC genes are significantly correlated with poor patient survival. Furthermore, ASIC1 inhibitors cause a significant reduction of tumor growth and tumor load. Together, these results suggest that ASIC1 contributes to breast cancer pathogenesis in response to acidic tumor microenvironments, and ASIC1 may serve as a prognostic marker and a therapeutic target for breast cancer.